2009
DOI: 10.4049/jimmunol.0900274
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage Delivery of Nanoformulated Antiretroviral Drug to the Brain in a Murine Model of NeuroAIDS

Abstract: Antiretroviral therapy (ART) shows variable blood-brain barrier penetration. This may affect the development of neurological complications of HIV infection. In attempts to attenuate viral growth for the nervous system, cell-based nanoformulations were developed with the focus on improving drug pharmacokinetics. We reasoned that ART carriage could be facilitated within blood-borne macrophages traveling across the blood-brain barrier. To test this idea, an HIV-1 encephalitis (HIVE) rodent model was used where HI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
188
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 209 publications
(189 citation statements)
references
References 76 publications
1
188
0
Order By: Relevance
“…Indeed, cell-based nanocarriers have been developed for not only cancer chemotherapy, but also a wide range of microbial infections (34)(35)(36). Macrophagebased nanomedicine delivery schemes may have several advantages over more conventional drug delivery, including enhanced cure rates, reduced side effects, increased drug stability, and effective subcellular targeting (26,27,37,38). Using macrophages as a nanocarriage vehicle can permit investigation of nanoATV entry, intracellular trafficking, and drug release kinetics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, cell-based nanocarriers have been developed for not only cancer chemotherapy, but also a wide range of microbial infections (34)(35)(36). Macrophagebased nanomedicine delivery schemes may have several advantages over more conventional drug delivery, including enhanced cure rates, reduced side effects, increased drug stability, and effective subcellular targeting (26,27,37,38). Using macrophages as a nanocarriage vehicle can permit investigation of nanoATV entry, intracellular trafficking, and drug release kinetics.…”
Section: Discussionmentioning
confidence: 99%
“…Cell nuclei were counterstained with hematoxylin for 60 s. Images were taken using a Nikon TE300 microscope with a 40ϫ objective. Quantitation of immunostaining was performed by densitometry using ImagePro Plus, v. 4.0 (27).…”
mentioning
confidence: 99%
“…4,11,12 Prior works demonstrated that such nanoART could be carried in monocyte-macrophages and reach viral sanctuaries. [11][12][13][14][15] These studies also showed that size, shape, and charge of crystalline indinavir (IDV), ritonavir (RTV), atazanavir (ATV), and efavirenz (EFV) affect uptake, release, cytotoxicities, and antiretroviral responses.…”
Section: Introductionmentioning
confidence: 99%
“…26 Nano-ART can be taken up within minutes by circulating monocytes and released in tissues over a period of 2 weeks. [56][57][58][59][60] Theoretically, cell-based nano-ART would travel to sites of inflammation and release drug(s) slowly with limited tissue toxicities. Such a drug-delivery system can revolutionize HIV-1 therapeutics and can particularly target virus sequestration.…”
Section: Targeted Drug Delivery Of Antiretroviralsmentioning
confidence: 99%
“…59 An elegant study using a nanosuspension of indinavir showed that macrophages loaded with this nanosuspension could bring about a measurable reduction in antiviral load in the brains of an HIV-infected rodent model. 56 Magnetic nanoformulations have been used for targeting active nucleotide analog reverse transcriptase inhibitors to the brain by application of an external magnetic force and thereby eliminating the brain HIV reservoirs. Our group has recently shown that conjugation with transferrin (Tf), allows antiretroviral drug-loaded nanoformulations to permeate across biological barriers such BBB via a receptor-mediated transport mechanism.…”
Section: Targeting Hiv-1 In the Brainmentioning
confidence: 99%